Hubungan Jarak Rumah ke Puskesmas dengan Kepatuhan Pengobatan Pasien Tuberkulosis Paru di Puskesmas Patokbeusi Subang - Riki Yudiana; Zulmansyah; Herry Garna (Bandung Conference Series: Medical Science, 2022)
Abstract. Tuberculosis is a chronic infectious disease caused by Mycobacterium tuberculosis which is chronic. Based on WHO Burden Disease data (2018), tuberculosis is the top 10 disease causing death. Drugs to reduce the eradication of tuberculosis are tablets of fixed dose combination anti-tuberculosis drugs (OAT-KDT). Non-adherence in undergoing treatment will cause resistance to OAT-KDT. The purpose of this study was to analyze the relationship between the distance from home to the puskesmas with adherence to taking OAT-KDT at the Subang Patokbeusi Public Health Center during February–June 2021. This type of research was quantitative with an observational analysis method with a cross-sectional approach. Data were obtained from medical records of tuberculosis patients period Januari 2020–Januari 2021. Data analysis used the chi-square test. If there are cells <5 then the Fisher exact test is used. The number of samples were 68 people. Processing and analyzing data used statistical application SPSS 25.00 for Mac with a significance degree of p<0.005. Pulmonary TB patients with a distance from home to the health center <5 km, 5–10 km, and >10 km who were adherence to taking medication, 30/31 people, 31/32 people, and 3/5 people (p=0.003) consequentially it means that there was a significant relationship. In conclusion, there is a relationship between the distance from the house to the puskesmas with the compliance of tuberculosis patients in undergoing treatment. Abstrak.Tuberkulosis adalah penyakit menular kronis yang disebabkan oleh Mycobacterium tuberculosis yang bersifat kronis. Berdasar atas data Burden Disease WHO (2018), tuberkulosis menjadi penyakit 10 teratas penyebab kematian. Obat untuk menurunkan eradikasi penyakit tuberkulosis, yaitu tablet obat anti-tuberkulosis kombinasi dosis tetap (OAT-KDT). Ketidakpatuhan dalam menjalani pengobatan akan menyebabkan resistensi terhadap OAT-KDT. Tujuan penelitian ini menganalisis hubungan jarak rumah ke puskesmas dengan kepatuhan meminum OAT-KDT di Puskesmas Patokbeusi Subang dilaksanakan Februari–Juni 2021. Jenis penelitian kuantitatif dengan metode observasional analisis dengan pendekatan cross-sectional. Data diperoleh dari medical record pasien tuberkulosis periode Januari 2020–Januari 2021. Analisis data menggunakan uji chi-square. Jika terdapat sel <5 maka digunakan uji Eksak Fisher. Jumlah sampel 68 orang. Pengolahan dan analisis data menggunakan aplikasi statistika SPSS 25.00 for Mac dengan derajat kemaknaan p<0,005. Pasien TB paru dengan jarak rumah ke puskesmas <5 km, 5–10 km, dan >10 km yang patuh meminum obat berturut-turut 30/31 orang, 31/32 orang, dan 3/5 orang (p=0,003) artinya terdapat hubungan bermakna. Simpulan, terdapat hubungan jarak rumah ke puskesmas dengan kepatuhan pasien tuberkulosis dalam menjalani pengobatan.